2008
DOI: 10.1037/0003-066x.63.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Improving the peer-review process for grant applications: Reliability, validity, bias, and generalizability.

Abstract: Peer review is a gatekeeper, the final arbiter of what is valued in academia, but it has been criticized in relation to traditional psychological research criteria of reliability, validity, generalizability, and potential biases. Despite a considerable literature, there is surprisingly little sound peer-review research examining these criteria or strategies for improving the process. This article summarizes the authors' research program with the Australian Research Council, which receives thousands of grant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
221
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(235 citation statements)
references
References 33 publications
(78 reference statements)
12
221
0
2
Order By: Relevance
“…Many manuscripts are rejected on this criterion, even if the reviewers identify the research as sound and reported effectively. Despite evidence of the unreliability of the review process for evaluation and identifying importance (Bornmann, Mutz, & Daniel, 2010;Cicchetti, 1991;Gottfredson, 1978;Marsh & Ball, 1989;Marsh, Jayasinghe, & Bond, 2008;Peters & Ceci, 1982;Petty, Fleming, & Fabrigar, 1999;Whitehurst, 1984), this is a reasonable criterion given that journals have limited space and desires to be prestigious outlets. However, in the digital age, page limits are an anachronism (Nosek & Bar-Anan, 2012).…”
Section: Journals With Peer Review Standards Focused On the Soundnessmentioning
confidence: 99%
“…Many manuscripts are rejected on this criterion, even if the reviewers identify the research as sound and reported effectively. Despite evidence of the unreliability of the review process for evaluation and identifying importance (Bornmann, Mutz, & Daniel, 2010;Cicchetti, 1991;Gottfredson, 1978;Marsh & Ball, 1989;Marsh, Jayasinghe, & Bond, 2008;Peters & Ceci, 1982;Petty, Fleming, & Fabrigar, 1999;Whitehurst, 1984), this is a reasonable criterion given that journals have limited space and desires to be prestigious outlets. However, in the digital age, page limits are an anachronism (Nosek & Bar-Anan, 2012).…”
Section: Journals With Peer Review Standards Focused On the Soundnessmentioning
confidence: 99%
“…** We were able to rule out that these evaluations were due to unequal gender representation in the review committee. On average, committees contained 32.6% female reviewers; the gender composition of the review committee was unrelated to application evaluations and success rates for male and female applicants (26,27) (SI Text and Fig. S1).…”
Section: Application Evaluations and Success Ratesmentioning
confidence: 99%
“…It means that published journal articles are valuable in a very concrete manner. They also serve as merits when applying for research funding or starting research projects (Marsh, Jayasinghe, & Bond, 2008). The term "publish or perish" has become more than familiar to researchers across the world (e.g., Ching, 2013;Roth 2002).…”
Section: The Pressure Of Publishingmentioning
confidence: 99%